Pengembangan Bioplastik Berbasis Pati dengan Penambahan Propilen Glikol sebagai Plasticizer - Agustina, Amelia Naomi; Nury, Dennis Farina; Nainggolan, Denny Hendrik (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The petrochemical industry plays an important role in the supply chain of polymer-based products. In terms of raw materials, this industry still relies heavily on fossil-based feedstocks whose availability is gradually declining. On the other hand, the products generated from this industry contribute to the increasing accumulation of plastic waste due to their resistance to natural degradation. Nevertheless, the demand for industrial sustainability continues to rise along with the increasing needs of society. The development of bioplastics can serve as one of the diversification strategies to produce value-added materials, specifically in biodegradability. This study aims to produce bioplastics using various type of starch and fillers with propylene glycol as a plasticizer and to analyze their characteristics. The results of this study indicate that the appropriate combination of starch, filler, and plasticizer can enhance the physical characteristics of bioplastics. The bioplastics produced using various combinations of starch types and fillers in this study were able to degrade, which is better than standard commercial bioplastics that had not degraded within seven days. However, further optimization of the formulation is still required to achieve physical characteristics that approach or meet the Indonesian National Standard (SNI).